Music Improvisation Is Characterized by Increase EEG Spectral Power in Prefrontal and Perceptual Motor Cortical Sources and Can be Reliably Classified From Non-improvisatory Performance - Sasaki, Masaru; Iversen, John; Callan, Daniel E. (Frontiers in Human Neuroscience, 2019)
This study explores neural activity underlying creative processes through the investigation of music improvisation. Fourteen guitar players with a high level of improvisation skill participated in this experiment. The experimental task involved playing 32 second alternating blocks of improvisation and scales on guitar. EEG data was measured continuously throughout the experiment. In order to remove potential artifacts and extract brain related activity the following signal processing techniques were employed: Band pass filtering, Artifact Subspace Reconstruction, and Independent Component Analysis. For each participant, artifact related ICs were removed from the EEG data and only ICs found to be from brain activity were retained. Source localization using this brain related activity was carried out using sLORETA. Greater activity for improvisation over scale was found in multiple frequency bands (theta, alpha, and beta) localized primarily in the medial frontal cortex MFG, anterior cingulate, polar medial prefrontal cortex, premotor cortex, pre and post central gyrus, superior temporal gyrus, inferior parietal lobule, and the temporal parietal junction. Together this collection of brain regions suggests that improvisation was mediated by processes involved in coordinating planned sequences of movement that are modulated in response to ongoing environmental context through monitoring and feedback of sensory states in relation to internal plans and goals. Machine-learning using common spatial patterns for EEG feature extraction attained a mean of over 75% classification performance for improvisation versus scale conditions across participants. These machine-learning results are a step towards the development of a brain computer interface that could be used for neuro-feedback training to improve creativity.